Clinical researchImpaired action of nitric oxide on blood platelets in premature newborns - Watała, Cezary; Chudzik, Anita; Tchórzewski, Henryk; Gwoździński, Krzysztof (Archives of Medical Science, 2008)
Introduction: The influence of nitric oxide (NO) on blood platelets in premature newborns remains largely unexplained. Material and methods: The expression of the activated GPIIb-IIIa complex and P-selectin were monitored by flow cytometry in whole blood platelets originating from 21 premature, 19 full-term neonates and 27 adults. Platelets were incubated with either freshly generated NO, L-arginine or NO donors (SNAP, GSNO) prior to their activation with collagen or ADP. Results: Platelets from preterm neonates showed extremely reduced reactivity compared to normal full-term neonates and adults, when activated by ADP, collagen or thrombin (P<0.001 or less). NO reduced reactivity of neonatal platelets activated with collagen to a lower extent compared to adult donors (up to 28-39% in full-term and 6-15% in preterm newborns compared to 25-49% in adults); the tendency was not so regular for ADP. The observed reduction in platelet function remained in proportion to newborns’ gestational age. Moreover, platelets from preterm neonates agonized with ADP showed reduced vulnerability to the action of L-NAME, an inhibitor of NO synthase, and L-cystamine, an inhibitor of guanylate cyclase. The immature responses in platelets from neonates, and especially preterm infants, are specific for various platelet activators, NO sources or modulators of the NO-dependent pathway. Conclusions: In spite of immaturity and reduced reactivity of platelets from newborns, their NO-dependent inhibition may be efficient to some extent even in most immature babies.